2-Local derivations on Schrödinger algebra in (2 + 1)- dimensional space-time. Issue 2 (1st February 2023) - Wang, Peng; Tang, Xiaomin
Abstract: The present paper is devoted to study 2-Local derivations on the Schrödinger algebra in (2 + 1)-dimensional space-time of Schrödinger Lie groups. We prove that every 2-local derivation on this algebra is a derivation.